Metaphor in learner and expert argumentative writing : A comparative corpus-dirven study - Chapetón Castro, Claudia Marcela (Tesis Doctorales, 2017)
Metaphors, it is well acknowledged by now, are fundamental in thought and in language, since they reflect the way we understand and organize the world. Conceptual metaphors underlie linguistic metaphors, which are ubiquitous in language. However, speakers use them very often unconsciously and most metaphors in our everyday language go unnoticed. This volume focuses on the use of metaphor in real language. Bearing very much in mind that a complete study of metaphor has to reflect its actual use by speakers rather than being based on introspection alone, and being aware of the danger of presenting decontextualized examples, in this book Chapetón combines a cognitive and a corpus-based applied linguistic approach and analyses the metaphoric expressions of three different corpora of argumentative texts. Willing to frame her research in an applied linguistic context and driven by her pedagogical interest in the teaching of English, Chapetón compares the differences and similarities of metaphoric production in a learner corpus of Spanish EFL students, a native corpus of American university students, and an expert corpus of American newspapers editorials. The contents of the book thus report results on the comparative analysis of the precense and nature of linguistic metaphor, metaphorical densities and frecuencies across corpora, the word class of metaphor, the precense and nature of animate metaphor and personification, the intertwined nature of animate metaphor and its textual roles and patterns. The book also discusses the different implications and potential applications of this comparative corpus-driven study on metaphors in language use. This book is an important contribution to the study of metaphor. It offers not only a deep analysis of the characteristics and complexities of metaphor in actual use, but also a model of research methodology. This publication will be of great interest to a wide readership including expert metaphor researchers, English Teachers, and postgraduate students.